2011
DOI: 10.3402/rlt.v19i3.17113
|View full text |Cite
|
Sign up to set email alerts
|

Technologies for learning? An actor-network theory critique of 'affordances' in research on mobile learning

Abstract: How is the link between learner and technology made in mobile learning? What is the value of the concept of 'affordances'? And how does research articulating this concept act to position mobile devices as 'technologies for learning'? This literature review used both unstructured and structured search samples of published research on mobile learning to critically evaluate the prevalence and influence of the concept of the affordances of mobile technologies. Actor-network theory is drawn on as a theoretical lens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Participant 2 confirms that the checklist’s affordances are relationally configured and would differ, if they were part of a different network of entities, shaped by different relations of power, which does not produce subjects who are ‘used to taking instructions’ (Bloomfield et al, 2010; Wright and Parchoma, 2011). The checklist is therefore implicated in the performance and regulation of employee identities (Symon and Pritchard, 2015), by attempting to produce ‘sustainable subjects’ and homogenize conduct in line with norms about sustainability.…”
Section: Generating a Boundary Object: Publicorg And The Affordances mentioning
confidence: 94%
See 1 more Smart Citation
“…Participant 2 confirms that the checklist’s affordances are relationally configured and would differ, if they were part of a different network of entities, shaped by different relations of power, which does not produce subjects who are ‘used to taking instructions’ (Bloomfield et al, 2010; Wright and Parchoma, 2011). The checklist is therefore implicated in the performance and regulation of employee identities (Symon and Pritchard, 2015), by attempting to produce ‘sustainable subjects’ and homogenize conduct in line with norms about sustainability.…”
Section: Generating a Boundary Object: Publicorg And The Affordances mentioning
confidence: 94%
“…For example, common workplace objects such as printers (usually affording ‘print-ability’), or car parking spaces (usually affording ‘park-ability’) might also afford new opportunities for learning about how to be sustainable in relation to energy and fuel consumption. Affordances have enabled scholars to examine the agential role of artifacts in mobile learning (Turner, 2005; Wright and Parchoma, 2011) and the ‘world-making’ activities of cultural practice (Sutherland, 2013). While some scholars define affordances as the essential, measurable properties of an object (Gibson, 1979), others consider them subjective, perceived characteristics (Norman, 1988) informed by the user’s experiences (Greeno, 1994) or familiarity with the object (Turner, 2005), and still more have suggested that understanding all the eventual affordances (perceived or real) of an object is impossible (Oliver, 2005; Wright and Parchoma, 2011).…”
Section: The Affordances Of Boundary Objects and The Politicization Omentioning
confidence: 99%
“…Many game-centered approaches would be examples of anti-schooler discourses. Wright and Parchoma (2011) use ANT in their review of mobile learning research, in which they problematize studies that position mobile devices as “technologies for learning.” In their view, not only are definitions of “affordance” inconsistently applied in the research, they point out that the “ubiquitous” nature of mobile devices is assumed to be inherent, unproblematic, and an obvious property of the technology. Mobile technology becomes a black box (Latour 1987, 2005) that outputs learning, while what actually goes on when people use mobile devices in the wild are obscured.…”
Section: Ant In Educationmentioning
confidence: 99%
“…They were not producers of content that might be shared in an online forum but they possessed specialized knowledge of the games they were playing. Concurrent with ongoing research on games, players, and participatory culture, more studies that examine how games fit into players’ lives can offer on-the-ground perspectives that are often lacking in educational technology research (Bigum et al., 2015; Selwyn, 2010, 2012; Wright and Parchoma, 2011). Researchers should also study more players who are different from themselves, who play games that researchers might not play, and include more games that are underrepresented in existing literature.…”
Section: Conclusion and Further Researchmentioning
confidence: 99%
See 1 more Smart Citation